Compression, expansion, or maybe both? Growing inequalities in lung cancer in Germany. - Fabian Tetzlaff; Jelena Epping; Heiko Golpon; Juliane Tetzlaff (PLoS ONE, 2020)
Background Lung Cancer (LC) is one of the most common malign diseases worldwide. So far, it is unclear if the development of LC incidence and mortality leads to morbidity compression or expansion and whether these developments differ by socioeconomic characteristics. This study analyses time trends in social and gender inequalities in life years with and without LC in Germany. Methods The study is based on data of a large German statutory health insurance provider (N = 2,511,790). Incidence and mortality risks were estimated from multistate survival models. Trends in life years with and without LC were analysed using multistate life table analyses. All analyses were performed separately for gender, time period (2006-2009 and 2014-2017), and income group (<60% and ≥60% of the German average income). Results Among men, declining LC incidence rates resulted in gains of life years free of LC and declining LC- affected life years and led to a relative compression, which was strongest in men with higher incomes. Among women, a clear increase in life years with LC led to an expansion of the lifespan affected by LC. This expansion was mainly driven by increasing incidence rates in women with low incomes. Overall, income inequalities in LC increased in both genders. Conclusions Our analyses reveal that developments in the length of life affected by LC differed substantially by gender and income and led to widening health inequalities over time. Public health efforts should mainly focus on vulnerable groups to reduce the persisting social inequalities in LC.